Models of knowledge management in micro and small enterprises (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
The paper analyzes models of knowledge management (KM), based on the profile of the micro and small enterprises (MSE) in the state of Sergipe, Brazil, specifically the models proposed by C. R. Silva Jr. (2006); E. E. Thiel (2002); M. C. Rumizen (2002) and G. Von Krogh and K. Ichijo and T. Nonaka (2000). The characteristics of the MSE in the Brazilian economy emphasize their place of prominence as responsible for 28% of gross revenues from the formal sector and 20% of Gross Domestic Product. However, the lack of researches which emphasize the reality of the MSE may be one reason which interferes in their more significant role in the Brazilian economy. The corpus consists of 60 (sixty) employees from 10 (ten) MSE installed in the Technological Park of Sergipe, incorporating managers, key professionals and members of the operating body. Through the techniques of interview, questionnaire and direct observation, it identifies the attributes of technology in the MSE, as well as the characteristics of the adopted processes and the ones considered ideal for employees. The most important results reveal the inadequacy of the analyzed models, because they are always elaborated by considering the reality of medium and big enterprises. It concludes, finally, that none of analyzed models are fully adequate to the reality of the MSE, and even the model of Von Kroch, Ichijo and Nonaka approaching closely to the profile of these companies, still requires modifications to its implementation. It is recommended, therefore, the creation of a model through further analysis of the activities from other adoption models to establish a new model suitable to the limitations of MSE. Keywords: Knowledge Management. KM. Micro and Small Enterprises. MSE. Models of Knowledge Management. Models of KM.Link para o texto completo (PDF)http://www2.marilia.unesp.br/revistas/index.php/bjis/article/view/2797/2462